Forty-five years of the journal “Cuadernos de Administración” - Universidad del Valle” By Milton Mora Lema. Founder of Cuadernos de Administración - Mora Lema, Milton (Cuadernos de Administración, 2021)
Forty-five years of existence of “Cuadernos de Administración” is and will always be a reason for celebration for the academy: The School of Administration and its Editors confirm their enthusiasm and conviction, by continuing to edit and successfully fulfilling the purpose for which they were created. The “Cuadernos” have been a means of information on scientific academic developments in the field of business administration and related areas of knowledge. For the authors and editors of this publication, the greatest satisfaction is knowing that their writings, periodic content, messages, findings and opinions have been understood, studied and applied. As readers, the motivation is to find great innovations in each edition, which will allow them to understand how to overcome the current challenges that they are currently experiencing in the fields of economics, business, management, as well as a guide on how to adapt to the new onus’s realities. And even more, to help you to plan the immediate future that serves as a guide to modern management and mainly in the different areas: public, industrial, commercial, health, justice and education. In short, we are always waiting for new information and guidance services to make the necessary decisions in the orientation and administration of organizations with leaders awarded to contribute the improvements of future societies. For the Founders of the magazine “Cuadernos” is an honor and pride, to celebrate forty-five years, from the first publication to see our dreams materialized and turned into such an impressive publication, reaching 45 years is the evidence of the great achievement, “ Having done it well”, that we celebrate today. In 1976 in the Department of Administration, with the collaboration of our Master Andrés Sevilla and the professor Leonel Monroy, we created: a means of communication and information of knowledge and academic developments. “Cuadernos” was part of the strategy and information medium of the innovations of our teachers, when we began to conceptualize and direct the New School of Administration in the 1970s. Andres Sevilla, Hugo Restrepo, Hernando Arellano, Jaime Lopez, Leonel Monroy, Leon Blank, Alberto Merlano, Alberto Guitis, Miguel Bernal, Octavio Garcia, Fabio Villegas, Jose Manuel Arenas, Hernan Alvarez, Harold Edgar Perea, Bernardo Barona, Ricardo Pabon, come to mind in these moments of celebration. To all of them, an immense gratitude for their support, collaboration - and for their contributions - in the realization of this academic strategic component. The results of “Cuadernos” in its forty-five years of existence have been reflected in the editions and articles of researchers, our university’s professors and business leaders, with national and international recognition, for the innovations presented, in the scientific field of business management. To all of them, our deepest gratitude for their work in the realization of our dreams, they have all played the role of managers and actors of this great academic educational development. Finally, like forty-five years ago, let me remember the projection of those dreams. we said at that time: “This is the first issue of the Cuadernos de Administración, a newsletter for teaching purposes, which we hope will become the magazine of the School of Management of the Universidad del Valle.” “The Department of Business Administration, which gave a decisive impetus to the administration of organizations in the region more than ten years ago, has since been constantly evolving; its task of producing knowledge to teach and to share it with other sectors of the university and the city through this means of information.” “Individuals inclined for the profession of business management have been helped by us to improve their knowledge in the field of the organization and its dynamic agent the administrator. We desire, in the years to come, to maintain the service of those whom we have served (our graduates) and will serve; similarly, to new sectors that have not had a link with the University; we want to be an authoritative voice in a society that must and needs to be well managed.” “One way to do this is by guiding, through qualified information, all those who run and manage organizations (public and private), with the desire to be used for their daily work, today and tomorrow. We want this to be your newsletter, for you to understand that it is, to feel it and to want it to be.” We hope in this way, through you, transcend the community.” Milton J. Mora Lema Cali, 1976. Let us now share some reflections that could contribute to the future of “Cuadernos” and its information mission in the field of Management, for the academic training of current and future generations. Clearly, in the last years of the 20th and 21st centuries, a transformative revolution has occurred in all fields and levels, from the individual to the organizational globalization of human talent. We, as actors and managers of new developments, must then reflect on how our present actions can impact the future, our environment and the quality of life of our children, relatives and living beings. And this means accepting responsibility for our decisions and actions in the face of these potential problems. It is necessary to become aware of the need to avoid the undesirable future and to choose other alternatives to obtain sustainable development. And from this vision, participate with reliable information that guides management training. Undoubtedly, the development and growth of contemporary societies are a consequence of the level of education, strategies and institutional educational models. In the field of management and business, educational models have contributed to the formation of leaders with levels of knowledge of contemporary organizations, aware of these realities and with the ability to analyze management decisions. In our case, “Cuadernos”, faithful to its development mission, will continue to maintain its leading role, providing information on research, knowledge innovations in Management and Management training and the like of the modern world. In this context, what should be its orientation to contribute to the solution of the main problems that we are experiencing, in Western societies, for example, in the management of ecosystems, in the quality of life of the surrounding societies, in modern management for companies and businesses in the industrial, commercial, public institutions, health, justice and other fields. What competencies, concepts and distinctive values are necessary to guide the formation of the leaders of the organizations, their ethical and human formation, that they contribute to consolidating justice and equity for their societies? The training of modern management must be aimed at contributing to the construction of a better world with quality of life for the benefit of all human beings and their ecosystems. What then will be the role of the “Cuadernos” of the future “? The knowledge, science and technology, in the world’s leading countries, have become strategies to generate new processes of political, educational and institutional development. Scientific and technological innovations, new knowledge and information have generated cultural changes, new technological developments applied to the innovation of new processes, new ways of working and major changes in contemporary organization, which have required the development of qualified human talent in these cutting-edge technologies. A society stronger in scientific and technological knowledge requires greater investments in education, research and development. There must be policies and strategies where the citizen can value the importance of knowledge and its application, based on the scientific and technological results generated in the country for the solution of real problems in Colombia today aggravated by the post-pandemic Covid 19. The use of technology is allowing us to solve the main challenges of the planet: feeding the entire population, to guarantee access to drinking water, education for all, sustainable energy and caring for the environment, among others. Within this trend, what should be the orientation of Cuadernos, to detect the new trends and innovations that have transformed, the economies, the management and administration of contemporary organizations? Of course, these challenges would imply being open to transform in the field of education, in the habitual mentalities, the strategies of the businesses and the styles of management. With educational innovations, online content is growing, and will continue in this trend improving, as well as, the obsolescence of knowledge every five years and the content of teaching changing every year. These challenges imply a revolution in the content and the media of Cuadernos? “Each edition of the journal Cuadernos would be full of: Timely research, relevant business and management advice, interesting case studies The participation of teachers and researchers will be the backbone of the Journal, with their contributions from the new findings, obtained in the doctorate and teaching research. This academic technological contribution, when applying science to practice, would lead to development, growth and would raise the levels of knowledge and training to the postgraduate and professional levels, as well as the quality of life. The content of our magazine would be designed to inform and inspire its readers to grow and achieve their individual goals. “ The above reflections would be a great challenge for the Faculty of Administration Sciences and therefore, for Cuadernos de Administración to continue and maintain its informative academic leadership. Playing the role of Alma Mater, spreading knowledge to sensitize and train its leaders and citizens, with training for modern management, administration and leadership solutions and developments. In this way, the “Cuadernos” magazine will continue to contribute to the economic, technological and cultural growth of its readers, fulfilling the mission for which they were created and also contributing to the development of the New Colombia that all Colombians yearn for. Let us keep making our dreams come true. Thanks.